2016 IEEE Intelligent Vehicles Symposium (IV) 2016
DOI: 10.1109/ivs.2016.7535428
|View full text |Cite
|
Sign up to set email alerts
|

Performance of current eco-routing methods

Abstract: Eco-routing is a vehicle navigation method that aims to minimize fuel or energy consumption for a given trip. It is based on a hypothesis that we can trade extra travel time for lower consumption. While the hypothesis was experimentally verified the design of a method that would fully exploit its potential proves challenging. Current solutions hinge on assumption that energy spent on any given road does not change in time. We challenge validity of this assumption by studying performance of such methods in deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Probabilistic approaches are a solution in case of lack of information about the vehicle dynamics. By construction, they are less accurate than models based on the actual speed, but can be effectively used to estimate emissions and energy consumption (Kubička et al, 2016). To improve these methods, traffic prediction models could be integrated to determinev (cf.…”
Section: Probabilistic Methodsmentioning
confidence: 99%
“…Probabilistic approaches are a solution in case of lack of information about the vehicle dynamics. By construction, they are less accurate than models based on the actual speed, but can be effectively used to estimate emissions and energy consumption (Kubička et al, 2016). To improve these methods, traffic prediction models could be integrated to determinev (cf.…”
Section: Probabilistic Methodsmentioning
confidence: 99%
“…By considering link-based variables, they can address driving heterogeneity, thus are more accurate than macroscopic models. However, most of the existing mesoscopic models for eco-routing use parametric regression-based models [12,13] or power balance models [14][15][16] and are not accurate enough due to the complexity of traffic scenario and nonlinearity of vehicle powertrains. Advanced data-driven methods such as support vector machines (SVM) [17], neural networks (NN) [18] and multivariate adaptive regression spline (MARS) [19] were also studied, and many outperformed the traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several routing algorithms have been proposed in the literature for conventional vehicles which are capable of finding the energy-optimal paths using historical and online traffic data [4]- [8]. Kubicka et al [9] performed a study to compare the objective values proposed in the eco-routing literature and showed that the performance of eco-routing algorithms is highly dependent on the method used to calculate the traveling cost of each link. Although eco-routing of conventional vehicles is well studied, there is little research that addresses the case of PHEVs [10].…”
Section: Introductionmentioning
confidence: 99%